Exertional heat stroke in an amateur runner – Challenges in diagnostics and the role of unhealthy competition. Issue 22 (16th November 2020) - Marlega, Joanna; Mickiewicz, Agnieszka; Fijalkowska, Jadwiga; Gruchala, Marcin; Fijalkowski, Marcin
ABSTRACT: Exertional heat stroke (EHS) is a potentially life-threatening condition with a variety of symptoms and abnormal laboratory findings. Nevertheless, data evaluating the course of making an EHS diagnosis in real-life practice, as well as the role of predisposing psychological components are limited. Thus, the aim of our study was to present a multi-faceted differentiation process and show the role of unhealthy competition in the development of EHS. We describe a case of a young amateur runner, admitted to the hospital due to loss of consciousness, further mental confusion, and increased body temperature above 40 ° C. Head scans excluded brain haemorrhage and stroke. Elevated troponin I levels suggested an acute coronary syndrome (ACS) or myocarditis. An increase of procalcitonin levels, signs of rhabdomyolysis and severe liver injury resulted in evaluation for infection and acute hepatic damage. Subsequently, the patient's negative results pointed us to a diagnosis of EHS. In-depth anamnesis revealed that the patient's excessive effort during the race was linked to the male-female competition. EHS can present diagnostic challenges, as it mimics various diseases, such as stroke, myocarditis, ACS, infection, or liver dysfunction. In addition, the role of psychological components, such as unhealthy competition, in the development of EHS should be considered.